Cemitérios rurais e rituais de morte na região de Barro Alto no sertão da Bahia – séculos XX e XXI - Coimbra, Glayce Rocha Santos (2021)
The imaginary of death involves representations that give meaning to the world and are constructed from the real and internalized in the social and historically in the collective unconscious. This thesis discusses the changes and permanence that characterize the universe of death in funerary rituals and in rural cemeteries. The main objective is to investigate the symbolism of death in the social imaginary of the inhabitants of the rural region of Bahia's hinterland and the social representations of funeral rituals that are still practiced in the 21st century, investigating how religious devotion is seen by most people as a form necessary to face death. The questions permeate in relation to funeral rituals, since the 19th century, which are still present in the social imagery related to death, in the towns of the city of Barro Alto (BA) and the way in which residents deal with cemeteries designed to preserve the memory of the dead, using symbolic and religious elements of the funerary rituals present in the region. As methodological procedures, several photographic surveys were carried out, documentary sources such as: death certificates, mortuary photographs, saints, video and oral interviews. The research data show that some funerary practices from the 19th century are still present today, and others, such as the singing of inselences and blessings, are being forgotten due to the lack of interest of the current generation. Rural cemeteries are maintained and cared for by the houses themselves and are considered spaces to represent memory.